Original paperThe assessment of subsegmental branches of the pulmonary artery by intravascular ultrasound in patients with mitral stenosis - Karapinar, Hekim; Kaya, Zekeriya; Açar, Göksel; Batukan Esen, Őzlem; Bulut, Mustafa; Küçükdurmaz, Zekeriya; Gül, Ibrahim; Yazıcıoğlu, Mehmet; Esen, Ali; Kirma, Cevat (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
Background: There are limited data that examine the assessment of subsegmental branches of the pulmonary artery by intravascular ultrasound (IVUS). Aim: To assess the structural characteristics of pulmonary arteries by IVUS in the setting of severe mitral stenosis. Material and methods : Twenty-one consecutive patients (3 men and 18 women; mean age: 38 ±11 years) who were selected for percutaneous mitral balloon valvuloplasty entered the study. Subsegmental branches of the right lower lobe pulmonary artery were imaged by 40 MHz IVUS when the patients underwent right heart catheterization. Minimal lumen diameter (MLD), external elastic membrane diameter (EEMD), lumen area (LA), and area circumscribed by the external elastic membrane (the total vessel area – TVA) were measured. From these measurements, wall area (WA = TVA – LA), intima-media wall thickness [IMT = (EEMD – MLD)/2], relative wall thickness (RWT = IMT/EEMD), and relative wall area (RWA = WA/TVA) were derived. Results: We were able to perform the IVUS examination in all patients without complications. Several IVUS anatomic indexes correlated with hemodynamic data. Pulmonary artery IMT, RWT, and RWA correlated significantly with pulmonary artery systolic pressure (r = 0.763, p = 0.002; r = 0.698, p = 0.001; r = 0.717, p = 0.006, respectively). However, there was no significant correlation between ultrasound measurements and echocardiographic parameters of the mitral valve. Conclusions: The subsegmental branches of the pulmonary artery can be assessed by IVUS. Patients with pulmonary hypertension in the setting of mitral stenosis have greater pulmonary arterial WT. The severity of WT is correlated with pulmonary artery pressure, but it is not associated with mitral valve area. Intravascular ultrasound may provide useful additional information in the management of patients with mitral stenosis.